Efektifitas Promosi Kesehatan Menggunakan Video Whatsapp untuk Meningkatkan Pengetahuan Pekerja Pelayanan Kesehatan tentang Disinfeksi Permukaan - Ristanti Apriyani; Heru Subaris Kasjono; Sigid Sudaryanto (Poltekkes Kemenkes Yogyakarta, 2021)
One of protection activities on Covid-19 transmission prevention is the disinfection of surfaces, rooms, and equipment periodically. One activity to strengthen the role of public health centre (puskesmas) which is related to Covid-19, is by increasing promotional and preventive activities among the community through communication, information and education. The purpose of this research is to examine the effectiveness of health promotional activities by using WhatsApp vi-deo on health cadres’ knowledge about surface disinfection. The study was a quasi experiment with non equivalent control group design. The respondents are 60 health cadres, who were di-vided into two groups, i.e. 30 in the treatment group with video, and the other 30 in the control group with picture. The intervention was conduted in three replications. Google form was used as the instrument for data collection. The results showed that both the WhatsApp video and pict-ure media improving the knowledge about surface disinfection (p <0,001). Descriptively, the increase in the video group was higher that that of the picture group. However, the difference was not statistically significant (p=0,596).